Frequency and Prognostic Significance of Abnormal Liver Function Tests in Patients With Cardiogenic Shock - Jäntti, Toni; Tarvasmäki, Tuukka; Harjola, Veli-Pekka; Parissis, John; Pulkki, Kari; Sionis, Alessandro; Silva-Cardoso, Jose; Køber, Lars; Banaszewski, Marek; Spinar, Jindrich; Fuhrmann, Valentin; Tolonen, Jukka; et al. (The American journal of cardiology, 2017)
Cardiogenic shock (CS) is a cardiac emergency often leading to multiple organ failure and death. Assessing organ dysfunction and appropriate risk stratification are central for the optimal management of these patients. The purpose of this study was to assess the prevalence of abnormal liver function tests (LFTs), as well as early changes of LFTs and their impact on outcome in CS. We measured LFTs in 178 patients in CS from serial blood samples taken at 0 hours, 12 hours, and 24 hours. The associations of LFT abnormalities and their early changes with all-cause 90-day mortality were estimated using Fisher's exact test and Cox proportional hazards regression analysis. Baseline alanine aminotransferase (ALT) was abnormal in 58% of the patients, more frequently in nonsurvivors. Abnormalities in other LFTs analyzed (alkaline phosphatase, gamma-glutamyl transferase, and total bilirubin) were not associated with short-term mortality. An increase in ALT of >20% within 24 hours (ΔALT>+20%) was observed in 24% of patients. ΔALT>+20% was associated with a more than 2-fold increase in mortality compared with those with stable or decreasing ALT (70% and 28%, p <0.001). Multivariable regression analysis showed that ΔALT>+20% was associated with increased 90-day mortality independent of other known risk factors. In conclusion, an increase in ALT in the initial phase was seen in 1/4 of patients in CS and was independently associated with 90-day mortality. This finding suggests that serial ALT measurements should be incorporated in the clinical assessment of patients in CS.
Keywords: Alkaline Phosphatase; Humans; alkalická fosfatasa; prevalence; Shock, Cardiogenic; Liver Diseases; Liver Function Tests; Female; jaterní testy; Aged; Alanine Transaminase; senioři; lidé; kardiogenní šok; Europe; nemoci jater; ženské pohlaví; Male; prognóza; incidence; Incidence; Prevalence; Prognosis; alanintransaminasa; míra přežití; mužské pohlaví; Evropa; Survival Rate